Immunomodulatory effect of Quercetin on dysregulated Th1/Th2 cytokine balance in mice with both type 1 diabetes and allergic asthma - Nutakki Ravikumar, Chilaka Naga Kavitha (Journal of Applied Pharmaceutical Science, 2020)
T-helper subtype imbalance is intricate in type 1 diabetes (T1D) and asthma initiation. The role of quercetin in immune dysregulation in comorbid conditions of T1D and asthma is not available. In this study, it was thought worthy to evaluate the role of quercetin on modulating Th1/Th2 cytokine dysregulation in comorbid diabetic asthma. Male Balb/c mice were injected intravenously with alloxan (80 mg/kg) to persuade T1D. Succeeding diabetes introduction, two intraperitoneal sensitizing doses of ovalbumin emulsion (50 μg ovalbumin blended with 2.5 mg alum/sensitization) were given on days 3 and 8. Mice were given intranasal challenges of ovalbumin (100 μg ovalbumin/25 μl of sterile saline) on days 13–15. Oral quercetin treatment (10–30 mg/kg) was given daily on days 3–15. Nasal hyperresponsiveness (NHR) was recorded immediately after Ova challenge on day 16. Bronchoalveolar lavage fluid (BALF), blood, and lungs were collected 1-hour post NHR for further analysis. Quercetin treatment significantly decreased eosinophils, interleukin-4 while increasing interferon-gamma in blood, and BALF and reduced the allergic airway inflammation by inhibiting inflammatory cell infiltration and mucous cell metaplasia. Furthermore, quercetin with a dose of 30 mg/kg demonstrated a significant glucose reduction. Thus, quercetin exerted dose-dependent anti-asthma activity by modulating Th1/Th2 balance with glucose-lowering potential in comorbid mice.
Keywords: Quercetin, Th1/Th2 balance, ovalbumin, comorbid diabetic asthma, allergic inflammation.